Detection of Human papillomavirus and co-infection with other sexually transmitted pathogens in northern Peru - Champin Michelena, Denisse Cecilie (2021)
[El documento adjunto corresponde al resumen de la conferencia. Se presenta en este apartado el propósito del estudio]: Purpose: The epidemiology of human papillomavirus (HPV) and co-infections with other sexually transmitted infections (STIs) remains poorly characterized in Peru. The aim of this study was to identify HPV infections and the presence of co-infections by other important STIs (Chlamydia trachomatis, Trichomonas vaginalis, and Herpes simplex virus) in women attending the public health system in northern Peru.